2020
DOI: 10.1177/1945892420914185
|View full text |Cite|
|
Sign up to set email alerts
|

Vascular Anatomy of the Inferior Turbinate and Its Clinical Implications

Abstract: Background Published reports on the vascular anatomy of the inferior turbinate (IT) are limited. Historical papers report the IT artery as a tributary off the posterior lateral nasal artery (PLNA), but this has not been our clinical experience. Objective The purpose of this study was to examine the arterial blood supply to and the branching pattern within the IT. We discuss this is the context of IT surgery and relate it to postoperative bleeding complication rates. Methods Endoscopic dissection was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A recent anatomical study showed that the primary blood supply of the inferior turbinate is through the descending palatine artery and its branches within the inferior turbinate. 5 These branches were observed in the periosteum when dissecting in the subperiosteal plane. The submucosal tissue underlying the mucosa is carefully resected while observing the contour and movement of the mucosa.…”
Section: Discussionmentioning
confidence: 98%
“…A recent anatomical study showed that the primary blood supply of the inferior turbinate is through the descending palatine artery and its branches within the inferior turbinate. 5 These branches were observed in the periosteum when dissecting in the subperiosteal plane. The submucosal tissue underlying the mucosa is carefully resected while observing the contour and movement of the mucosa.…”
Section: Discussionmentioning
confidence: 98%
“…Care should be taken not to damage the descending palatine and branches from the glossopharyngeal nerve as this may result in palatal paresthesia. During PNN, division of the SPA is also controversial with some surgeons recommending it and others not 20,21 . Failure to divide the SPA may result in the preservation of a significant number of PPG nerve fibers that run with the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…During PNN, division of the SPA is also controversial with some surgeons recommending it and others not. 20 , 21 Failure to divide the SPA may result in the preservation of a significant number of PPG nerve fibers that run with the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Other exciting and impactful articles are presented in the realm of CRS, including the Roland et al 13 study that seeks to characterize CRS with nasal polyp subtypes based on radiographic imaging and the Schertzer et al 14 study by the same group, which describes the prevalence of comorbid allergic rhinitis and the predictable anatomic location of respiratory epithelial adenomatoid hamartoma (REAH) that is also present in central compartment atopic disease. Cadaveric studies by Li et al 15 and Scott et al 16 elegantly describe the prelacrimal approach to access the antero-lateral triangle of the middle cranial fossa 15 and the blood supply to the inferior turbinate from the descending palatine artery, which may be utilized in the reconstruction of anterior skull base defects. 16 This issue promises to engage the reader in a range of interesting and innovative topics, which has become the hallmark of AJRA.…”
mentioning
confidence: 99%
“…Cadaveric studies by Li et al 15 and Scott et al 16 elegantly describe the prelacrimal approach to access the antero-lateral triangle of the middle cranial fossa 15 and the blood supply to the inferior turbinate from the descending palatine artery, which may be utilized in the reconstruction of anterior skull base defects. 16 This issue promises to engage the reader in a range of interesting and innovative topics, which has become the hallmark of AJRA. We trust that you will find it useful in advancing your understanding of the topics that continue to provide challenges in the care of rhinologic disease.…”
mentioning
confidence: 99%